The Knowledge of Teachers about Rights of Children to Reducing Child Abuse in Homeless Students - Shahnaz Rahpaymaelizehee, Masoumeh Pourrajab, Bahare Fallahi, Shah (Journal of Educational, Health and Community Psychology, 2014)
AbstractÂ The aim of this review paper is to identify the important role of teachers about reporting child abuse in their classroom to reduce and prevention of child abuse with considers the homeless students. The findings of this study show that teachers have an important role to intervene and prevent of child abuse, because they spend a lot of time with students and contact with them in classroom. This study also finds that, teachers believed that the appropriate training has not been taught them in colleges, universities or teachers training centers. Furthermore, this paper pursues the professional abilities of teachers in order to find the child abuse signs of their students as well as the homeless ones and the skills of reporting them.Â Key word: Child Abuse, Homeless Students, Knowledge, Teacher, Report